Short-Term Measurement Repeatability of a Simplified Intravoxel Incoherent Motion (IVIM) Analysis for Routine Clinical Diffusion-Weighted Imaging in Malignant Liver Lesions and Liver Parenchyma at 1.5 T - Pieper, Claus Christian; Sprinkart, Alois Martin; Kukuk, Guido Mattias; Mürtz, Petra (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Objectives To evaluate measurement repeatability of parameters derived from simplified intravoxel incoherent motion (IVIM) analysis of diffusion-weighted imaging (DWI) using 3 b-values.Materials and Methods 24 patients (16 male, 8 female, mean age: 67 years) with hepatic malignancy (HCC: 10, metastases: 14) underwent 29 liver MRI examinations at 1.5 T. Respiratory-triggered DWI (b = 0, 50, 800 s/mm2) was acquired twice. Parameter maps of the apparent diffusion coefficient ADC(0,800), estimated diffusion coefficient D' and perfusion fraction f' were calculated. Measurement repeatability for a region of interest (ROI) placed in one lesion and liver parenchyma per lobe was assessed by intra-session variation coefficients (CV).Results 86 ROIs (43 lesions, 43 parenchymas) were analyzed. Parameters did not significantly differ between measurements. Repeatability was excellent for ADC(0,800) and D' and good for f' in parenchyma (CVs: 7.3 %, 9.8 %, 13.0 %) and lesions (CVs: 7.5 %, 8.5 %, 11.0 %). Differences in CV-values between liver and lesions were not significant. Repeatability was better for the right than for the left lobe by tendency, for parenchyma (CVs: 6.4 % vs 8.4 %, 8.8 % vs 10.9 %, 10.5 % vs 16.0 %) and for lesions (CVs: 6.9 % vs 8.1 %, 7.5 % vs 9.5 %, 9.5 % vs 12.7 %).Conclusion Measurement repeatability is excellent for ADC(0,800) and D' values and good for f' values using the simplified IVIM approach, both in lesions and liver parenchyma. Repeatability was better for lesions in the right compared to the left liver lobe.Key points: Citation Format
Keywords: MR-diffusion/perfusion; liver tumors; technical aspects